In vitro and in vivo evidence that the antiviral activity of 2',3'-dideoxycytidine is target cell dependent in a feline retrovirus animal model. - Polas, P J (1990)
2',3'-Dideoxycytidine (DDC) was evaluated for prophylactic antiviral activity in vitro and in vivo, using the feline leukemia virus (FeLV)-cat animal model. In vitro antiviral activity of DDC against FeLV was dependent upon the target cell used for infection. DDC (5 to 10 microM) inhibited FeLV infection of feline lymphoid cells by greater than 80%, while 6.07 to 12.13 microM DDC was required to similarly inhibit infection of feline fibroblasts. However, 43 to 384 microM DDC was needed to inhibit FeLV infection of primary bone marrow cells by greater than 80%. These in vitro results suggest that, although relatively low doses of DDC may be adequate to prevent infection of feline lymphoid cells, 8- to 80-times-higher doses may be necessary to block infection of bone marrow cells, a primary target cell type for FeLV infection. In vivo studies with DDC consisted of pharmacokinetic and toxicity determinations and evaluation of the prophylactic antiviral activity against FeLV in cats. Clearance and half-life values for DDC in cats were 6.5 ml/min per kg and 54.7 min, respectively. In the prophylactic studies, DDC was administered by continuous intravenous infusion at doses of 22, 15, 10, and 5 mg/kg per h for 28 days in most animals. Cats were challenged intravenously with FeLV 1 to 3 days after drug treatment began. Doses of 22 and 15 mg/kg per h were extremely toxic, causing death in 8 of 10 cats. The mg/kg per h dose was slightly toxic, causing chronic progressive thrombocytopenia over the 28-day treatment period. Of 10 cats given 10 to 5 mg of DDC per kg per h, only one was completely protected from FeLV antigenemia. However, conversion to positive FeLV antigenemia status was delayed by 2 to 7 weeks in seven of nine remaining animals. Interestingly, FeLV infection of bone marrow cells, as indicated by FELV antigen in peripheral blood neutrophils, was only slightly delayed by 0 to 2 weeks, except in the case of the one protected cat, and usually preceded conversion to antigenemia. This pattern of neutrophils becoming antigen positive before detection of antigenemia was not seen in FeLV challenge control animals and indicates that the antiviral activity of DDC may be incomplete during DDC treatment. Results of our in vitro and in vivo studies suggest that feline bone marrow cells may remain partially susceptible to FeLV infection at tolerated doses, while other somatic target tissues (i.e., lymphoid or epithelial tissues) may be protected from infection. Incomplete inhibition of FeLV infection permitted focal bone marrow infection to develop in cats given DDC. These loci of infection served as virus reservoirs which, subsequent to discontinuation of DDC treatment, permitted spread of infection to tissues previously protected during treatment.